An Isolated Nitridyl Radical-Bridged {Rh(N.)Rh} Complex - Gloaguen, Yann; Rebreyend, Christophe; Lutz, Martin; Kumar, Pravin; Huber, Martina; van der Vlugt, Jarl Ivar; Schneider, Sven; de Bruin, Bas (Angewandte Chemie International Edition, 2014)
Photochemical activation of [(PNNH)Rh(N3)] (PNNH=6‐di‐(tert‐butyl)phosphinomethyl‐2,2′‐bipyridine) complex 2 produced the paramagnetic (S=1/2), [(PNN)RhN.‐Rh(PNN)] complex 3 (PNN−=methylene‐deprotonated PNNH), which could be crystallographically characterized. Spectroscopic investigation of 3 indicates a predominant nitridyl radical (.N2−) character, which was confirmed computationally. Complex 3 reacts selectively with CO, producing two equivalents of [(PNN)RhI(CO)] complex 4, presumably by nitridyl radical N,N‐coupling. The first isolated nitridyl radical (.N2−) complex was obtained by photochemical activation of the rhodium–azide complex [(PNNH)Rh(N3)] (1), producing N2, H2, and the paramagnetic complex 2. Complex 2 reacts selectively with CO to produce complex 3, presumably by N,N‐coupling of nitridyl radicals.